2014
DOI: 10.1074/jbc.m114.606269
|View full text |Cite
|
Sign up to set email alerts
|

Complex N-Linked Glycans Serve as a Determinant for Exosome/Microvesicle Cargo Recruitment

Abstract: Background: Exosomes/microvesicles (EMVs) transport protein cargo between cells effecting cell-cell communication.Results: Alteration of N-link glycans controls recruitment of specific proteins (e.g. EWI-2) into EMVs. Conclusion: N-Linked glycosylation is a key determinant of glycoprotein sorting into EMVs.Significance: This is the first demonstration that N-linked glycans mediate protein sorting to EMVs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
120
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(125 citation statements)
references
References 59 publications
4
120
0
1
Order By: Relevance
“…Glycosylation also plays a role in the expression and sorting of other exosomal proteins. For example, sorting of the protein EWI-2 into exosomes is dependent on the presence of complex N-linked glycans on this protein (21). Mutation of even one of three N-linked glycosylation sites significantly decreased EWI-2 expression in extracellular vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…Glycosylation also plays a role in the expression and sorting of other exosomal proteins. For example, sorting of the protein EWI-2 into exosomes is dependent on the presence of complex N-linked glycans on this protein (21). Mutation of even one of three N-linked glycosylation sites significantly decreased EWI-2 expression in extracellular vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…These data are also consistent with the findings of Nyalwidhe et al 35 who reported a decrease in fucosylation in the glycan spectra of pooled expressed prostatic secretions in urine. Also other studies reported that a loss of N-glycosylation was linked to an altered protein trafficking to extracellular vesicles in PCa21 as well as in other malignancies, for example, ovarian cancer 36…”
Section: Discussionmentioning
confidence: 94%
“…However the mechanism, leading to which proteins are selected for exosomal transport in normal conditions or in cancer, remains elusive. Increased exosomal expression of certain proteins could be related to their asparagine (N)-linked glycan carbohydrate structures as it has been proven that N-glycosylation plays an important role in protein subcellular transport and secretion 21. However, literature on the relationship between extracellular vesicles and N-glycosylation patterns is scanty.…”
Section: Introductionmentioning
confidence: 99%
“…The unique lipid, glycan, protein, and miRNA components of exosomes reflect their cancer type origins and are attractive targets for development of biomarkers, especially miRNAs. A recent study has linked larger branched sialylated glycans as determinants of glycoproteins that become exosome/microvesicle constituents (Liang et al, 2014), a theme also observed in exosomes derived from clinical prostatic secretions representing the most advanced prostate cancers (Nyalwidhe et al, 2013). Exosomes, being a major carrier of miRNAs and prevalent in clinical fluids, and the glycomic composition of their constituent glycoproteins appear to be a unique nexus of genomics, proteomics, and glycomics that can be targeted for further biomarker assay development.…”
Section: Emerging Areasmentioning
confidence: 99%
“…The implications that tumor cells modulate miRNA networks to alter glycosylation profiles associated with cancer development and progression could be a transformative concept that will need to be assessed in each type of cancer for similarities and differences in miRNA participants. Another emerging area that merges all of the "omics" discussed is that of glycosylation in cancer exosomes/microvesicles (Drake et al, 2015;Drake & Kislinger, 2014;Liang et al, 2014). The unique lipid, glycan, protein, and miRNA components of exosomes reflect their cancer type origins and are attractive targets for development of biomarkers, especially miRNAs.…”
Section: Emerging Areasmentioning
confidence: 99%